Management of Nonmalignant Tracheo- and Bronchoesophageal Fistula after Esophagectomy - Palmes, Daniel; Kebschull, Linus; Bahde, Ralf; Senninger, Norbert; Pascher, Andreas; Laukötter, Mike G.; Eichelmann, Ann-Kathrin (The Thoracic and Cardiovascular Surgeon, 2020)
Background Tracheo- or bronchoesophageal fistula (TBF) occurring after esophagectomy represent a rare but devastating complication. Management remains challenging and controversial. Therefore, the purpose of this study was to evaluate the outcome of different treatment approaches and to propose recommendations for the management of TBF.Methods From 2008 to 2018, 15 patients were treated because of TBF and were analyzed with respect to fistula appearance, treatment strategy (stenting, endoscopic vacuum therapy and/or surgical reintervention) and outcome.Results In each case, the fistula was small, located close to the tracheal bifurcation and associated simultaneously (n = 6, 40%) or metachronously (n = 9, 60%) with an anastomotic leakage. Latter was covered by esophageal stents in six patients which in turn resulted in occurrence of TBF at a later time in five patients. Management of TBF included conservative therapy (n = 3), stenting (n = 6), or suturing (n = 6). Ten patients underwent rethoracotomy. Treatment failure was observed in eight patients (53%). In all patients, treatment was accompanied by progressive sepsis. On the contrary, all seven patients with successful defect closure remained in good general condition.Conclusion Fistula appearance was similar in all patients. Implementation of esophageal stents cannot be recommended because of possibility of TBF at a later time point. Surgery is usually required and should preferably be performed when the patient's condition has been optimized at a single-stage repair. Esophageal diversion can only be recommended in patients with persisting mediastinitis. The key element for successful treatment of TBF, however, is control over sepsis; otherwise, outcome of TBF is devastating.
Keywords: esophageal; airways; bronchial; reoperation; stents; surgery; complications